Gaseous NO2 induces various envelope alterations in Pseudomonas fluorescens MFAF76a - Thibault Chautrand; Ségolène Depayras; Djouhar Souak; Tatiana Kondakova; Magalie Barreau; Takfarinas Kentache; Julie Hardouin; Ali Tahrioui; Olivier Thoumire; Yoan Konto-Ghiorghi; Corinne Barbey; Guy Ladam; et al. (Scientific Reports, 2022)
Abstract Anthropogenic atmospheric pollution and immune response regularly expose bacteria to toxic nitrogen oxides such as NO• and NO2. These reactive molecules can damage a wide variety of biomolecules such as DNA, proteins and lipids. Several components of the bacterial envelope are susceptible to be damaged by reactive nitrogen species. Furthermore, the hydrophobic core of the membranes favors the reactivity of nitrogen oxides with other molecules, making membranes an important factor in the chemistry of nitrosative stress. Since bacteria are often exposed to endogenous or exogenous nitrogen oxides, they have acquired protection mechanisms against the deleterious effects of these molecules. By exposing bacteria to gaseous NO2, this work aims to analyze the physiological effects of NO2 on the cell envelope of the airborne bacterium Pseudomonas fluorescens MFAF76a and its potential adaptive responses. Electron microscopy showed that exposure to NO2 leads to morphological alterations of the cell envelope. Furthermore, the proteomic profiling data revealed that these cell envelope alterations might be partly explained by modifications of the synthesis pathways of multiple cell envelope components, such as peptidoglycan, lipid A, and phospholipids. Together these results provide important insights into the potential adaptive responses to NO2 exposure in P. fluorescens MFAF76a needing further investigations.